2018
DOI: 10.3847/1538-3881/aaa3e4
|View full text |Cite
|
Sign up to set email alerts
|

The K2-HERMES Survey. I. Planet-candidate Properties from K2 Campaigns 1–3

Abstract: Accurate and precise radius estimates of transiting exoplanets are critical for understanding their compositions and formation mechanisms. To know the planet, we must know the host star in as much detail as possible. We present first results from the K2-HERMES project, which uses the HERMES multi-object spectrograph on the Anglo-Australian Telescope to obtain R∼28,000 spectra of up to 360 stars in one exposure. This ongoing project aims to derive self-consistent spectroscopic parameters for about half of K2 ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 74 publications
(73 reference statements)
0
57
0
Order By: Relevance
“…If available and not flagged, stellar parameters from a prior version of The Cannon (version 1.3) are chosen. This version was also used for previous data releases of GALAH (Martell et al 2017), TESS-HERMES (Sharma et al 2018), and K2-HERMES (Wittenmyer et al 2018). If these parameters are flagged or not available, the synthesis commences with the stellar parameter estimates from the reduction process.…”
Section: Analysis Step 1: the Training Set Analysis With Spectroscopymentioning
confidence: 99%
“…If available and not flagged, stellar parameters from a prior version of The Cannon (version 1.3) are chosen. This version was also used for previous data releases of GALAH (Martell et al 2017), TESS-HERMES (Sharma et al 2018), and K2-HERMES (Wittenmyer et al 2018). If these parameters are flagged or not available, the synthesis commences with the stellar parameter estimates from the reduction process.…”
Section: Analysis Step 1: the Training Set Analysis With Spectroscopymentioning
confidence: 99%
“…The spectroscopic data used here is taken from an internal release of GALAH DR2, which includes, public data (Buder et al 2018, DR2 ), and fields observed as part of the K2-HERMES (Wittenmyer et al 2018) and TESS-HERMES Table 2. Parameters for the isolated Galaxy (Model P).…”
Section: Galah Dr2 Sample With Elemental Abundancesmentioning
confidence: 99%
“…We now have a large sample of stars with very precise metallicity measurements from spectroscopic surveys like the Galactic Archaeology for HERMES (GALAH De Silva et al 2015) , K2-HERMES (a GALAH-like survey dedicated to K2 follow-up, Wittenmyer et al 2018) and Apache Point Observatory Galactic Evolution Experiment (APOGEE Ma-jewski et al 2017) surveys. In this paper, we use data from the GALAH survey to determine the metallicity distribution of the stellar populations in the Besançon-based Galactic model that we later use for asteroseismic analysis.…”
Section: Introductionmentioning
confidence: 99%